In Memory of Acad. NAS of Ukraine, Prof. Bohdan Ostafiychuk - PCSS, Editorial_Team (Physics and Chemistry of Solid State, 2024)
Professor, Doctor of Physical and Mathematical Sciences, Corresponding member of the National Academy of Sciences of Ukraine, OSTAFYCHUK Bohdan Kostyantynovych (1948-2024)